'Because then you could never ever get a job!': children's constructions of NAPLAN as high-stakes. Issue 5 (3rd September 2017) - Howell, Angelique
Abstract: In the midst of the debate surrounding the question of whether Australia's National Assessment Program: Literacy and Numeracy (NAPLAN) test is high-stakes, it is evident that children's own accounts of their experiences remain sparse. This paper describes the findings of a case study which documented the experiences of 105 children across two Catholic primary schools in Queensland serving different socio-economic status (SES) communities. Analysis of the data revealed that these teachers and principals did not experience NAPLAN as high-stakes. However, the data suggested that the children experienced the tests within a confusing context of contradictions and dissonances emanating from multiple sources; receiving little, if any, clear and consistent information regarding the purpose and significance of NAPLAN. While the children's responses were varied, many reported NAPLAN as a negative experience, with some constructing the test as high-stakes. These constructions ranged from personal judgement or sense of letting their families down, to failure, and less commonly, grade retention and school exclusion. Some Year 3 children had also constructed good results as vital to future prosperity. These constructions bring into question the assumption that because NAPLAN is designed to be a low-stakes test, that children will necessarily experience it in this way.